Determinant of HDI in Yogyakarta Special Region Province (Universitas Negeri Semarang, 2022)
Yogyakarta Special Region (DIY) occupies the second position of high categorical HDI in Indonesia. The UMP, which is the benchmark for the number of wages given to workers, has the lowest amount in Indonesia. Several other factors that were thought to have influenced the high in HDI were inflation, GRDP, and LFPR. This study aims to determine and analyze the factors that influence HDI in DIY. The type of data used in this study is secondary data. The data used are sourced from BPS, Indonesian Statistics Report, Yogyakarta Labour Affair Office and GlobalDataLab. The research method used is multiple regression analysis time series for the period 1990-2019 DIY. The variables used in this study are HDI, Inflation, GRDP, UMP, and LFPR. The results showed that inflation has a negative and not significant effect on HDI. GDRP, UM,P and LFPR have a positive and significant effect on HDI. Daerah Istimewa Yogyakarta (DIY) menempati posisi IPM tinggi kedua di Indonesia. UMP yang menjadi tolak ukur besarnya upah yang diberikan kepada pekerja memiliki besaran paling rendah di Indonesia. Beberapa faktor lain yang diduga mempengaruhi tingginya IPM adalah inflasi, PDRB dan TPAK. Penelitian ini bertujuan untuk mengetahui dan menganalisis faktor-faktor yang mempengaruhi IPM di DIY. Jenis data yang digunakan bersumber dari BPS, Laporan Statistik Indonesia, Dinas Tenaga Kerja DIY dan GlobalDataLab. Metode penelitian yang digunakan adalah analisis regresi berganda time series periode 1990-2019 DIY. Variabel yang digunakan dalam penelitian ini adalah IPM, Inflasi, PDRB< UMP dan TPAK. Hasil penelitian menunjukkan bahwa inflasi berpengaruh negatif dan tidak signifikan terhadap IPM. PDRB, UMP dan TPAK berpengaruh positif dan signifikan terhadap IPM.